2015
DOI: 10.1007/s10926-015-9614-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Support Tools for Selecting Interventions for Patients with Disabling Musculoskeletal Disorders: A Scoping Review

Abstract: Purpose We aimed to identify and inventory clinical decision support (CDS) tools for helping front-line staff select interventions for patients with musculoskeletal (MSK) disorders. Methods We used Arksey and O’Malley’s scoping review framework which progresses through five stages: (1) identifying the research question; (2) identifying relevant studies; (3) selecting studies for analysis; (4) charting the data; and (5) collating, summarizing and reporting results. We considered computer-based, and other availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 153 publications
0
26
0
Order By: Relevance
“…Web-based tools such as computerized decision support systems are one of the most effective strategies to support the implementation of clinical pathways and guidelines, thereby improving HCP practice [24-26]. In musculoskeletal health, these tools are used to provide clinical information, guide triage, and match patients to appropriate resources and treatments [27]. These tools are shown to be effective in improving HCP practice in the management of conditions such as hypertension, diabetes, and osteoarthritis [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Web-based tools such as computerized decision support systems are one of the most effective strategies to support the implementation of clinical pathways and guidelines, thereby improving HCP practice [24-26]. In musculoskeletal health, these tools are used to provide clinical information, guide triage, and match patients to appropriate resources and treatments [27]. These tools are shown to be effective in improving HCP practice in the management of conditions such as hypertension, diabetes, and osteoarthritis [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study which explored the effectiveness of a decision-aid over usual care on patient satisfaction and physical outcomes in a sample of patients with non-specific low back pain found comparable satisfaction levels, but worse outcomes (pain/physical aspects) and lower cost-effectiveness for the intervention arm! [28] Considering that in musculoskeletal rehabilitation, decision-aids remain scarce and described to be in their developmental phase, they might be seen as premature to implement in clinical practice [29]. Furthermore, they are likely to remain scarce since we don't fully understand our own intervention effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although the interview remains the main way to gather information about the relative contribution/presence of occupation-related elements, a very recent scoping review found interesting tools. 97 Among others, the Work Assessment Triage Tool 98 captures 18 variables related to injury duration, job, working status, and availability of modified work. According to the patient/therapist response, it suggests best work reintegration options.…”
Section: Domains and Their Operational Definitionsmentioning
confidence: 99%